Definition of Phonetics and Aspects of its Study - kizi, Umarova Mohinur Sirojiddin (Researchparks Publishing, 2023)
The article contains general concepts about phonetics, information about problems related to learning phonetics. In addition, the definition given by scientists to phonetics, the problems and aspects of its study are presented.